FROM PERSONAL COMPUTER TO FACEBOOK: INFORMATION AND COMMUNICATION TECHNOLOGY AND ENGLISH WRITING RESEARCH - Mahardika, I Gusti Ngurah Agung Wijaya (Institut Hindu Dharma Negeri Denpasar, 2019)
This paper describes several research conducted in the area of Information and Communication Technology and English Writing. The aim of this paper is to paint a picture about the kind of technology used in writing which caught the attention of researchers. It covers the trend of ICT utilization in English writing from 1990s to date, as well as delineating the future research areas in this field. It covers the research on the use of Word Processor, Blog, and Facebook in English writing teaching and research.As described herein, the use of technology especially ICT goes hand in hand with the development of humanity including in the field of education. In English writing the future will only see more pervasive and intensive use of ICT in education including in English writing classes.